2022
DOI: 10.3389/fendo.2022.1041379
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index has a non-linear association with three-month outcomes in men with acute ischemic stroke: An analysis based on data from a prospective cohort study

Abstract: ObjectiveDespite reports of a connection between body mass index (BMI) and stroke outcome, the findings remain debatable. In this investigation, we sought to determine whether BMI was associated with the probability of 3-month unfavorable outcomes in patients with acute ischemic stroke (AIS).MethodsThis is a second analysis based on a cohort study. 1,897 people with AIS who were treated at a hospital in South Korea from January 2010 to December 2016 were included in the study. The linear relationship between B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In the diabetic group, AIS patients with HbA1c < 6.0% had the highest levels of Scr, C-reactive protein, the lowest HGB, and the highest percentage of hypertension. These are risk factors for adverse outcomes in AIS patients [ 18 , 24 , 25 ]. Therefore, in order to reduce the risk of adverse clinical outcomes, HbA1c should ideally be controlled at around 6.1% in diabetic patients with AIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the diabetic group, AIS patients with HbA1c < 6.0% had the highest levels of Scr, C-reactive protein, the lowest HGB, and the highest percentage of hypertension. These are risk factors for adverse outcomes in AIS patients [ 18 , 24 , 25 ]. Therefore, in order to reduce the risk of adverse clinical outcomes, HbA1c should ideally be controlled at around 6.1% in diabetic patients with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated effect sizes with 95% confidence intervals (95%CI). Confounding variables were adjusted based on clinical knowledge, literature reports, and univariate analysis results [ 17 , 18 ]. Additionally, TC was excluded from the final multivariate logistic regression equation due to collinearity with other factors (Table S 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, interactions and stratified analyses were conducted, as previously described. In addition, we investigated potential unobserved confusion between the TyG Index and carotid plaque by calculating the E-value 28 29. Statistical software packages R (http://www.R-project.org.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the BMI category of underweight in both sexes is also associated with a higher risk of ischemic stroke, and this category has a significantly higher rate of poor short and long-term outcomes than the BMI category of normal weight 9,10,11 . Other studies regarding the association between BMI and the prognosis after acute ischemic stroke have shown that BMI has a non-linear association with 3-month outcomes in men with acute ischemic stroke 8 , and that the BMI categories of underweight and obesity were generally associated with poorer outcomes 12,13,14 .…”
Section: Introductionmentioning
confidence: 92%
“…3. According to a previous meta-analysis 4, the risk of stroke is positively correlated with BMI, and this correlation is stronger in men and patients with ischemic stroke. The findings of yet another study supported this meta-analysis, revealing that the BMI categories of overweight and obesity were associated with an increased risk only in men 5. It has been shown that there is a positive correlation between the whole range of BMI categories and ischemic stroke 6 , with no evidence of a threshold or a J-shaped curve 7,8 . Conversely, the BMI category of underweight in both sexes is also associated with a higher risk of ischemic stroke, and this category has a significantly higher rate of poor short and long-term outcomes than the BMI category of normal weight 9,10,11 .…”
Section: Introductionmentioning
confidence: 99%